Immigrant adolescents' perceptions of cultural pluralism climate: Relations to self‐esteem, academic self‐concept, achievement, and discrimination. Issue 177 (4th May 2021) - Oczlon, Sophie; Bardach, Lisa; Lüftenegger, Marko
Abstract: A cultural pluralism climate values differences between groups and fosters learning about different cultures. This study investigated the relation between four facets of cultural pluralism climate (learning about multicultural topics, learning about intercultural relations, interest shown by teachers, interest shown by non‐immigrant students) and immigrant students' self‐esteem, academic self‐concept, achievement and perceived discrimination. We furthermore tested whether academic self‐concept, self‐esteem, and perceived discrimination mediated the relation between the four facets and achievement. Relying on a sample of 700 immigrant students ( M age = 12.62 years; SD = 1.12; 45.4% female) from 87 Austrian secondary school classes, all effects were estimated at two levels (L1, individual student level; L2, classroom level) in multilevel mediation models. It was shown that learning about multicultural topics and intercultural relations, and interest shown by teachers positively predicted academic self‐concept and self‐esteem at L1. Learning about intercultural relations negatively predicted discrimination at L1. At L2, learning about intercultural relations positively predicted academic self‐concept and negatively predicted perceived discrimination. None of the facets predicted achievement at L1 and L2. However, academic self‐concept (positively) and self‐esteem (negatively) fully mediated the effect of learning about multicultural topics, learning about intercultural relations, and interest shown by teachers on achievement at L1.